Estimating the Contributions of Rare and Common Genetic Variations and Clinical Measures to a Model Trait: Adiponectin. Issue 1 (2nd October 2012) - An, S. Sandy; Palmer, Nicholette D.; Hanley, Anthony J. G.; Ziegler, Julie T.; Brown, W. Mark; Haffner, Steven M.; Norris, Jill M.; Rotter, Jerome I.; Guo, Xiuqing; Chen, Y.‐D. Ida; Wagenknecht, Lynne E.; Langefeld, Carl D.; et al.
<x xml:space="preserve">Abstract</x> Common genetic variation frequently accounts for only a modest amount of interindividual variation in quantitative traits and complex disease susceptibility. Circulating adiponectin, an adipocytokine implicated in metabolic disease, is a model for assessing the contribution of genetic and clinical factors to quantitative trait variation. The adiponectin locus, ADIPOQ, is the primary source of genetically mediated variation in plasma adiponectin levels. This study sought to define the genetic architecture of ADIPOQ in the comprehensively phenotyped Hispanic (n = 1, 151) and African American (n = 574) participants from the Insulin Resistance Atherosclerosis Family Study (IRASFS). Through resequencing and bioinformatic analysis, rare/low frequency (<5% MAF) and common variants (>5% MAF) in ADIPOQ were identified. Genetic variants and clinical variables were assessed for association with adiponectin levels and contribution to adiponectin variance in the Hispanic and African American cohorts. Clinical traits accounted for the greatest proportion of variance (POV) at 31% (P = 1.16 × 10−47) and 47% (P = 5.82 × 10−20), respectively. Rare/low frequency variants contributed more than common variants to variance in Hispanics: POV = 18% (P = 6.40 × 10−15) and POV = 5% (P = 0.19), respectively. In African Americans, rare/low frequency and common variants both contributed approximately equally to variance: POV = 6% (P = 5.44 × 10−12) and POV = 9% (P = 1.44 × 10−10), respectively. Importantly, single low frequency alleles in each ethnic group were as important as, or more important than, common variants in explaining variation in adiponectin. Cumulatively, these clinical and ethnicity‐specific genetic contributors explained half or more of the variance in Hispanic and African Americans and provide new insight into the sources of variation for this important adipocytokine.